Effect of Plasticizer Glycerin on wood based technology - Abdul Aziz, Nabihah (2019)
Thermoplastic starch (TPS) was made by corn starch and mixed wood sawdust. There are three samples that used 30 % corn starch 70% mixed wood sawdust, 50% corn starch 50% mixed wood sawdust and 70% corn starch 30% mixed wood sawdust. The effect are tested by Thermogravimetric analysis ( TGA ), Scanning electron microscope ( SEM ), Fourier transform infrared spectroscopy ( FTIR ) and the physical test are tensile test, bending test and density test. Biodegradable plastic is plastic that decomposes naturally in the environment. This is achieve when microorganisms in the environment metabolize and break down the structure of biodegradable plastic. The end result is one which is less harmful to the environment than traditional plastics. Biodegradable plastics can be composed of bio-plastics which are plastics made from renewable raw materials. There are normally two forms of biodegradable plastic, injection molded and solid. The solid forms normally are used for items such as food containers, leaf collection bags and water bottles.